Barcode-Based Light Fire Extinguisher (APAR) Monitoring with the Waterfall Case Study Method of PT. PLN (Persero) UPK Nagan Raya - Hasanusi Pane; Gaustama Putra (LPPM Politeknik Aceh Selatan, 2023)
Light Fire Extinguishers (APAR) play a very important role in a company, this aims to prevent and overcome in the event of a fire. The development of technology for equipment inspection has now begun to use digital methods including using android applications and barcodes to facilitate the fire extinguisher inspection process. In this study, it uses the waterfall method, which is a technical model in software development, where a project will be detailed sequentially. Based on the results of research, a method of monitoring the fire extinguisher using androite-based barcodes that can be accessed through the internet network anytime and anywhere. This barcode-based monitoring method can minimize officer errors in writing data on the results of checking the fire extinguisher, searching for data on the results of the fire extinguisher check and can be viewed and accessed easily. Barcodes have been affixed to each fire extinguisher and the barcode has been designed complete with a description of the state of the fire extinguisher in it, including the type of fire extinguisher, weight, name of the officer, expiret, type. It can be concluded by using this method the quality of the resulting system will be better because its implementation is carried out gradually or sequentially.